Industrial training report: Kemaman Supply Base (Kemaman) / Robiatul Adawiyah Zukfile - Zukfile, Robiatul Adawiyah (Perpustakaan Tengku Anis, 2017)
The Industrial Training Report based on the period. From 1st February 2017 to 30th June 2017 in Information Technology (IT) Department at Pangkalan Bekalan Kemaman Supply Base at Eastern Pacific Industrial Corporation (Epic) Company Berhad. In this company, the trainee have discussed with her organization supervisor who was Mrs. Normah Bt Ibrahim as an Assistant Manager IT Pangkalan Bekalan Kemaman Sdn. Bhd. The task are planned properly starting. From the beginning of internship. Including the special project task that has been assigned by supervisor on the starting of internship. All the activities has been recorded in log book as an evidence for students in completing the period of industrial training. Gaining some experience required her a new lesson for every day they on internship.